Microflora of Drainage from Ice in Fishing Vessel Fishholds - Chen, Hsing-Chen (1982)
The microbial load in ice-melt drainage collected from fishholds of fishing vessels stowing lizard fish, black croakers, cuttle fish, or nemipterids was very high, ranging from 2.1 × 10(7) to 2.2 × 10(9)/ml for bacteria and 6.3 × 10(3) to 7.2 × 10(4)/ml for yeasts and molds. Analysis of 100 colonies each randomly isolated from drainage samples of cuttle fish and lizard fish showed that the occurrence of bacterial genera as a percentage of the total was Moraxella-Acinetobacter, 61 to 62%; Pseudomonas, 19 to 21%; Alcaligens, 5 to 10%; Flavobacterium, 1 to 4%; Micrococcus, 1 to 4%; Bacillus, Vibrio 0 to 2%; Corynebacterium, 1 to 2%; and others, 1 to 2%. The organisms demonstrated versatile hydrolytic activities to a wide range of biological substrates including casein, gelatin, starch, DNA, and RNA. The possible connection between these bacteria and the deterioration of fish quality are discussed.